STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM PEMBINAAN NILAI-NILAI RELIGIUS DI LINGKUNGAN MADRASAH ALIYAH MUSLIM CENDIKIA BENGKULU TENGAH - Dewi Ratna Furi (UIN Fatmawati Sukarno Bengkulu, 2019)
The study aims to find out the strategy of Madrasah principal education in the fostering of religious values in Madrasah Aliyah Muslim Cendikia Bengkulu Tengah, responses and funds of Madrasah shareholders in the development of religious values, as well as factors anything that becomes a role in the fostering of religious values in the madrasah Aliyah Muslim Cendikia Bengkulu Tengah. This research uses qualitative descriptive method. The research data were collected using interview, observation and documen techniques. The data collected from the technique is analyzed by using data reduction, data presentation and data verification, data validity is obtained by using data triangulation. The results of this study indicate that leadership strategy of head master in religious values development in Islamic madrasah Aliyah Cendikia Bengkulu Tengah used several strategies such as: habituation strategy, exemplary strategy and partnership strategy. In the guidance of religious values in madrasah, madrasah stake holders respond positively to the head master by demonstrating their respective commit- ments. The inhibiting or temptation factor in religious values in Madrasah Aliyah Muslim Cendikia from the basic education of diverse teachers and facilities and infrastructure that has not been maximized. The final Conclusion can be stated that the head master strategies in guiding islamic religious values at Madrasah Aliyah Muslim Cendikia have positive findings For madrasah stakeholders.